Evaluation of graphene oxide, chitosan and their complex as antibacterial agents and anticancer apoptotic effect on HeLa cell line - Ashry, Noha M.; El Bahgy, Halla E. K.; Mohamed, Abdelkader; Alsubhi, Nouf H.; Alrefaei, Ghadeer I.; Binothman, Najat; Alharbi, Mona; Selim, Samy; Almuhayawi, Mohammed S.; Alharbi, Mohanned T.; Nagshabandi, Mohammed K.; Saad, Ahmed M.; et al. (Frontiers in Microbiology, 2022)
Cancer and bacterial infection are the most serious problems threatening people's lives worldwide. However, the overuse of antibiotics as antibacterial and anticancer treatments can cause side effects and lead to drug-resistant bacteria. Therefore, developing natural materials with excellent antibacterial and anticancer activity is of great importance. In this study, different concentrations of chitosan (CS), graphene oxide (GO), and graphene oxide-chitosan composite (GO-CS) were tested to inhibit the bacterial growth of gram-positive (Bacillus cereus MG257494.1) and gram-negative (Pseudomonas aeruginosa PAO1). Moreover, we used the most efficient natural antibacterial material as an anticancer treatment. The zeta potential is a vital factor for antibacterial and anticancer mechanism, at pH 3–7, the zeta potential of chitosan was positive while at pH 7–12 were negative, however, the zeta potential for GO was negative at all pH values, which (p < 0.05) increased in the GO-CS composite. Chitosan concentrations (0.2 and 1.5%) exhibited antibacterial activity against BC with inhibition zone diameters of 4 and 12 mm, respectively, and against PAO1 with 2 and 10 mm, respectively. Treating BC and PAO1 with GO:CS (1:2) and GO:CS (1:1) gave a larger (p < 0.05) inhibition zone diameter. The viability and proliferation of HeLa cells treated with chitosan were significantly decreased (p < 0.05) from 95.3% at 0% to 12.93%, 10.33%, and 5.93% at 0.2%, 0.4%, and 0.60% concentrations of chitosan, respectively. Furthermore, CS treatment increased the activity of the P53 protein, which serves as a tumor suppressor. This study suggests that chitosan is effective as an antibacterial and may be useful for cancer treatment.